Gene expression in salivary glands: effects of diet and mouse chromosome 17 locus regulating macronutrient intake. Issue 2 (23rd February 2015) - Simon, Jacob; DiCarlo, Lisa M.; Kruger, Claudia; Johnson, William D.; Kappen, Claudia; Richards, Brenda K.
Abstract Dcpp2, Prrt1, and Has1 are plausible candidate genes for the Mnic1 (macronutrient intake‐carbohydrate) locus on mouse chromosome 17, based on their map positions and sequence variants, documented expression in salivary glands, and the important role of saliva in oral food processing and taste. We investigated the effects of genotype and diet on gene expression in salivary glands (parotid, submandibular, sublingual) of carbohydrate‐preferring, C57BL6J.CAST/EiJ‐17.1 subcongenic mice compared to fat‐preferring wild‐type C57BL/6J. To achieve accurate normalization of real‐time quantitative RT‐PCR data, we evaluated multiple reference genes to identify the most stably expressed control genes in salivary gland tissues, and then used geometric averaging to produce a reliable normalization factor. Gene expression was measured in mice fed different diets: (1) rodent chow, (2) macronutrient selection diets, (3) high‐fat diet, and (4) low‐fat diet. In addition, we measured salivary hyaluronan concentrations. All three genes showed strain differences in expression, in at least one major salivary gland, and diet effects were observed in two glands. Dcpp2 expression was limited primarily to sublingual gland, and strongly decreased in B6.CAST‐17.1 subcongenic mice compared to wild‐type B6, regardless of diet. In contrast, both genotype and diet affected Prrt1 and Has1 expression, in a gland‐specific manner, for example, Prrt1 expression in the parotid gland alone was strongly reduced in both mouse strains when fed macronutrient selection diet compared to chow. Notably, we discovered an association between diet composition and salivary hyaluronan content. These results demonstrate robust effects of genetic background and diet composition on candidate gene expression in mouse salivary glands.